Understanding Achilles' Heel: Information Dissemination, Readability, and Marketing in Urban School Choice. Issue 8 (November 2019) - Delale-O'Connor, Lori
Scholars have long acknowledged that the information parents have about schools is the "Achilles' heel" of school choice. Although much has been written about school choice, far less is known about the information disseminated to help families make choices. I construct a case study of the dissemination and accessibility of choice information in the Chicago Public Schools. I find that both the readability and content of the information disseminated limit its usefulness. In addition, a lack of centralized resources leads to both limited and disparate access. I conclude with modifications for improving information dissemination and accessibility.